[PP.38.06] LOW INTENSITY ISOMETRIC HANDGRIP EXERCISE HAS NO TRANSIENT EFFECT ON BLOOD PRESSURE IN PATIENTS WITH CORONARY ARTERY DISEASE. (September 2016) - Goessler, K.; Buys, R.; Cornelissen, V.
Abstract : Objective: Hypertension is highly prevalent among patients with coronary artery disease. Exercise-based cardiac rehabilitation is known to reduce blood pressure (BP). However, less is known about the transient effect of a single bout of exercise. Isometric handgrip exercise has been proposed as a non-pharmacological tool to lower BP, but his potential has not yet been evaluated in patients with coronary artery disease. Therefore the purpose of this study was to investigate the acute effect of low intensity isometric handgrip exercise on BP measured shortly after exercise in the office and during the subsequent 24 hours during daily life activities in stable patients with coronary artery disease. Design and method: Design: Randomized controlled cross-over design Methods: Twenty one male patients (median age 68; range 55–70) with stable, medicated, coronary artery disease participating in a phase III cardiac rehabilitation program were included in this study. All patients completed two experimental sessions in random order: one control session and one low intensity isometric handgrip session. BP was measured by means of a 24 h ambulatory blood pressure monitor pre-intervention, for one hour in the office and subsequently for 24 hours during their routine daily practice. At the same time, physical activity was assessed by means of a SenseWear mini device. Results: Results: Baseline resting BP averaged 136.1 ± 11.1/78.3 ± 6.8 mmHg and was similar at both test occasions (p > 0.05). Following the experimental sessions, we observed a time-effect for office BP and HR (p < 0.001 for all) which was not different on both testing days (p-interaction > 0.05 for all). During normal daily activities, no significant differences between both test days was found in 24 h, daytime and nighttime BP and HR (p > 0.05 for all). No adverse events occurred. Conclusions: Conclusions: Isometric handgrip exercise performed at low intensity is safe in physically active patients with stable coronary artery disease and does not induce a transient reduction in BP during daily life activities. Further research investing the longer-term effects of isometric handgrip training in patients with CAD is warranted.